Linking Individual Patient Data to Estimate Incidence and Prevalence of Parkinson's Disease by Comparing Reports of Neurological Services and Pharmacy Prescription Refills at a Nationwide Level - Szatmári, Szabolcs; Ajtay, András; Bálint, Mónika; Takáts, Annamária; Oberfrank, Ferenc; Bereczki, Dániel (Frontiers in Neurology, 2019)
Objectives: we set forth to estimate the number of those with Parkinson’s disease (PD) in Hungary, a country with a single-payer health insurance system covering 10 million inhabitants. Methods: we analyzed all hospital and outpatient reports from neurological services and pharmacy reports of prescription refills. We cross-checked clinically administered diagnosis of PD with prescription refills of antiparkinsonian medications using recorded linkage. We used the ICD-10 code of G20 in any diagnostic category to find all cases with possible PD. For case certification those patients were considered to have PD who were recorded with G20 code in at least 2 calendar years. For a more conservative estimation we determined the number of those who also refilled antiparkinsonian medication. Results: between 2010 and 2012 there were 46,383 subjects with certified PD by clinical criteria. Crude and age-standardized incidence were 49/100,000/year (95% CI: 45-53), and 56/100,000/year (95% CI: 51-60). Crude and age standardized prevalence rates were 404/100,000 (95% CI: 392-416) and 471/100,000 (95% CI: 456-485). Of all clinically certified PD patients 72% refilled antiparkinsonian medications. Discussion: the incidence and prevalence of PD in Hungary is higher than earlier estimates, which should be considered in organizing healthcare services for this patient group.